Calvarial osteomyelitis in secondary syphilis: evaluation by MRI and CT, including cinematic rendering - Petroulia, Valentina (Heliyon, 2020)
This is a case of a 22-year-old, HIV-negative, male patient with asymptomatic syphilitic osteomyelitis of the skull in the context of secondary syphilis. The diagnosis was made based on serology as well as CT and MRI scans. CT volumetric data was post-processed with cinematic rendering, which is a novel algorithm that allows for a photorealistic visualization of the lesions. Imaging and follow-up scans after treatment confirmed the diagnosis without the need to perform invasive procedures such as a biopsy.